Pemberian Terapi Relaksasi Nafas Dalam Terhadap Kondisi Ansietas Pasien Dengan Hipertensi - Damayanti, Evi; Sundari, Ririn Isma (Fakultas Kesehatan Universitas Muhammadiyah Sukabumi, 2022)
The elderly are a vulnerable group who often experience anxiety. Anxiety experienced by the elderly is caused by the presence of several health problems that accompany one of them is hypertension. Anxiety in the elderly with hypertension is associated with complications that may occur, such as heart failure, stroke, myocardial infarction to death. The purpose of this study was to describe the nursing care process for hypertensive patients with anxiety using deep breathing therapy interventions. The research design uses a descriptive method with a case study approach in hypertensive elderly who experience anxiety. Data obtained by conducting interviews, observation and physical examination. Giving deep breathing intervention for 3 visits showed that the anxiety problem was partially resolved. This condition can be seen from the decrease in the level of anxiety, the patient looks more relaxed and does not show any anxiety. The results of the case studies are expected to be a motivation in the management of anxiety in hypertensive patients so as to prevent further complications. And can be used as a reference for providing further interventions to be modified with other interventions in the management of anxiety.